Modeling, dynamics and control of spacecraft relative motion in a perturbed keplerian orbit - Okasha, Mohamed Elsayed Aly Abd Elaziz; Newman, Brett (The Korean Society for Aeronautical & Space Sciences, 2015)
The dynamics of relative motion in a perturbed orbital environment are exploited based on Gauss’ and Cowell’s variational equations. The inertial coordinate frame and relative coordinate frame (Hill frame) are used, and a linear high fidelity model is developed to describe the relative motion. This model takes into account the primary gravitational and atmospheric drag perturbations. Then, this model is used in the design of a navigation, guidance, and control system of a chaser vehicle to approach towards and to depart from a target vehicle in proximity operations. Relative navigation uses an extended Kalman filter based on this relative model to estimate the relative position/velocity of the chaser vehicle with respect to the target vehicle. This filter uses the range and angle measurements of the target relative to the chaser from a simulated LIDAR system. The corresponding measurement models, process noise matrix, and other filter parameters are provided. Numerical simulations are performed to assess the precision of this model with respect to the full nonlinear model. The analyses include the navigation errors and trajectory dispersions.